Evaluation of Turner Syndrome Knowledge among Physicians and Parents - Berna Eroğlu Filibeli; Nesrin Havare; Huriye Erbak Yılmaz; Jülide Gülizar Yıldırım; Gönül Çatlı; Bumin N. Dündar (Galenos Yayincilik, 2020)
Objective:Turner syndrome (TS) is one of the most common chromosomal abnormalities and an important cause of short stature and infertility due to ovarian failure in females. The aim was to evaluate the knowledge of TS among physicians and parents of children with TS and to enhance awareness about this subject.Methods:One hundred and forty physicians were included in the study. The study population comprised 37 pediatricians (26.4%), 15 gynecologists (10.7%), 88 family physicians (62.9%) and 30 parents who had daughters with a diagnosis of TS. Two separate questionnaires were administered to evaluate TS knowledge of physicians and parents.Results:According to the self-reports of physicians, 49% had insufficient knowledge of TS, while 15.7% indicated that they had no knowledge of TS. The mean percentage of correct answers was 50.71±16.17% for all physicians. When the entire group of physicians was considered, 67.1% of them did not know the approximate incidence of TS, while 14.3% of them incorrectly indicated that TS was a condition that was seen in boys. The mean percentage of correct answers among parents was 68±15%, and there was no difference between the mothers' and fathers' correct answer rates (p=0.063). The majority of parents was not aware of TS-associated diseases and increased malignancy risk in TS.Conclusion:Physician knowledge of TS was poor and that there is a need for continued education about TS at the medical faculty and post-graduate levels.